Research of the influence of highcarbon steel wire drawing speed on stresses and deformations on wire cross section - Yu. L. Bobarikin; Yu. V. Martyanov (Литьë и металлургия, 2019)
The parameters of wire production affecting the distribution of residual stresses and strains on the wire cross section are considered. It is determined that the modes of coarse drawing can affect the complex of mechanical properties of thin wire due to the uneven distribution of equivalent stresses and strains. The rough drawing speed is chosen as the investigated parameter.The effect of the coarse drawing rate of high-carbon steel wire on the distribution of equivalent residual stresses and strains over the wire cross section is studied by numerical simulation of wire drawing at different speeds by the finite element method. The values of equivalent residual stresses for the selected drawing route along the wire cross-section zones are determined. The analysis of the equivalent stress distribution over the wire cross section is made.It is shown that the increase in the speed of coarse drawing increases the uniformity of the distribution of equivalent residual stresses, does not have a negative effect on the deformed state of the wire, increases the absolute values of equivalent residual stresses, slightly reduces the absolute values of residual deformations.